Context matters: alibi strength varies according to evaluator perspective - Sommers, Samuel R. (Legal and criminological psychology, 2007)
Purpose. The nascent field of alibi evaluation research has produced interesting and inconsistent findings. We focus on a heretofore unexamined variable that may play a critical role in alibi evaluation: context. Specifically, two experiments tested the hypothesis that the same alibi can be evaluated differently when presented in the context of a police investigation vs. criminal trial. Method. In Study 1, 101 college participants evaluated an alibi in one of three contexts: police investigation, criminal trial, or a control condition devoid of specific legal context. Dependent measures included ratings of alibi strength and credibility, as well as the likelihood that the suspect was guilty. In Study 2, both context and the presence of a corroborating witness were varied in a scenario presented to 139 college participants. Results. Across studies, an alibi was rated as stronger in the police investigation vs. trial context, consistent with the prediction that the fact that a case has proceeded to trial implies to perceivers that the alibi is relatively weak. In Study 2, an alibi was deemed stronger when corroborated vs. uncorroborated, but this difference was only significant in the police investigation context. Conclusions. If alibi research is to fulfil its promise for legal and policy implications, a clearer understanding of the variables that influence alibi evaluation must be developed. The present results illustrate the importance of context in this investigation, suggesting that two researchers studying evaluations of the same alibi may arrive at different conclusions based on the simple framing of the experimental task.